Hedgehog Pathway Inhibitors and Their Utility in Basal Cell Carcinoma: A Comprehensive Review of Current Evidence - Evelyn Yu-Xin Tay; Yee-Leng Teoh; Matthew Sze-Wei Yeo (Adis, Springer Healthcare, 2018)
Abstract Basal cell carcinoma (BCC) is the most commonly diagnosed malignancy in humans, and as such it poses a significant healthcare burden. The majority of BCC cases are amenable to cure by surgical extirpation. However, until recently there have been no good treatment options for a significant minority of advanced BCC cases, including locally advanced BCC and metastatic BCC. The introduction of a novel class of drugs, the Hedgehog pathway inhibitors, into clinical practice has ushered in a new treatment algorithm for the treatment of difficult BCC cases. In this review we present the latest available evidence and discuss areas for further research in this rapidly evolving field.